HUBUNGAN PENGETAHUAN MASYARAKAT DENGAN SELF AWARENESS RISIKO DIABETES MELITUS TIPE 2 - Ikshan, Ikshan; Siswandi, Iyar (Faculty of Health Science and Technology, University of Jenderal Achmad Yani, 2024)
Background : Diabetes mellitus is a progressive disease characterized by the body's inability to metabolize carbohydrates, fats and proteins. Diabetes can be prevented by doing primary prevention (education) which can be given to people who have not suffered but have risk factors for diabetes mellitus prevention can start from yourself or self-awareness. Objective : The purpose of this study was to determine the relationship between community knowledge and self awareness of the risk of type 2 diabetes mellitus in the working area of banjar agung village, serang city. Method : This research method uses a correlational description research design and uses a cross sectional research approach. By using a knowledge and self awareness questionnaire. The population in this study were people who had a risk of type 2 diabetes mellitus with purposive sampling technique so that the sample in this study amounted to 96 respondents. Data collection using questionnaire sheets distributed directly. Data analysis was performed using the Chi-Square statistical test. Results : The results obtained by the study showed that there was a significant relationship between community knowledge and self awareness of the risk of type 2 diabetes mellitus (p value 0.001) also obtained OR value = 14.1. Suggestions for health workers can provide more education to people who have a risk of type 2 diabetes mellitus about what type 2 diabetes mellitus is and how to prevent it.